Empowerment of MSME groups through the CSR program "Duri Mas (Durian Mesu Andalan Sejahtera)” PT. Pertamina Patra Niaga animation fuel terminal depati amir in Air Mesu Village, Central Bangka Regency - Zhomah, Zhomah; Ulfa, Noppitri (Priviet Social Sciences Journal, 2025)
The Duri Mas (Durian Mesu Andalan Sejahtera) program is a Corporate Social Responsibility (CSR) program implemented by PT Pertamina Patra Niaga Aniantion Fuel Terminal Depati Amir in collaboration with the Air Mesu Village Government to develop the potential of local plants into various food products that have additional selling value. This program focuses on empowering MSME groups in the community by providing facilities, cooking equipment, and knowledge and skills in the process of product processing to marketing. The method used in this study is qualitative, with data collection techniques through unstructured interviews, observation, and documentation. The results of the study showed that this program has been running for three years, which has increased the amount of production by three times, energy efficiency by 40% in the production process, reduced the behavior of the younger generation in carrying out illegal tin mining, and increased awareness of protecting the natural environment through the cultivation of quality durian plants.